Psychosocial factors in sports injury rehabilitation and return to play - Podlog, L.; Heil, J.; Schulte, S. (Physical Medicine & Rehabilitation Clinics of North America, 2014)
This article discusses the principles and practices that guide psychological intervention with injury, and encourages a psychological approach to injury for clinicians. Part 1 reviews the research literature, and serves as a foundation for the review of clinical practices in part 2. Examination of the research literature highlights 4 areas: (1) psychological factors influencing rehabilitation, (2) social factors affecting rehabilitation, (3) performance concerns among returning athletes, and (4) tools/inventories for assessing psychological readiness to return. A synopsis of an injury intervention plan is provided, and the influence of pain and fear in the rehabilitation process is described.